Development of Interactive Learning Media Based on Articulate Storyline Using Group Type Cooperative Learning Model Investigation to Improve Students' Learning Outcomes on The Reaction Rate Material - Agustina Ruthlita Sirait; Haqqi Annazili Nasution (Universitas Lampung, 2025)
This study uses the Research and Development (R&D) method with the ADDIE (Analyse, Design, Develop, Implement and Evaluate) development model. The data collection technique uses the percentage technique of media expert and material expert validation sheets. In addition, using student response questionnaires and test questions. The results of the study showed that the interactive articulate storyline learning media obtained a media expert validity score of 4.15 out of a maximum score of 5.00 while the material expert validity was 4.72 out of a maximum score of 5.00. Interactive learning media has also been tested and obtained an average increase in learning outcomes of 48.19, from the previous average of students in the pretest of 31.94 increasing to 80.13 in the posttest. And based on the N-Gain test analysis, an average increase in overall learning outcomes of 0.70 was obtained, which experienced an increase in the High category. Based on these results, it can be concluded that the articulate storyline media for reaction rate material is categorized as very valid, very practical, and good for use in high school chemistry learning.